CPAP failure in the management of preterm neonates with respiratory distress syndrome where surfactant is scarce. A prospective observational study - Yaser Abdallah; Martha Mkony; Mariam Noorani; Robert Moshiro; Mohamed Bakari; Karim Manji (BMC, 2023)
Abstract Background The mainstay in the management of preterm neonates with respiratory distress syndrome (RDS) include early Continuous Positive Airway Pressure (CPAP), timely surfactant replacement and mechanical ventilation. Preterm neonates with RDS who fail CPAP are at higher risk for chronic lung disease as well as death. Unfortunately, in low resource settings CPAP may be the only treatment available for these neonates. Objective To determine the prevalence of CPAP failure among premature newborns with RDS and associated factors. Methods We conducted a prospective observational study over the first 72 h of life on 174 preterm newborns with RDS receiving CPAP at Muhimbili National Hospital (MNH). At MNH newborns with Silverman Andersen Score (SAS) of ≥ 3 are commenced on CPAP; surfactant and mechanical ventilation are very scarce. Study newborns not maintaining oxygen saturation > 90% or with SAS score ≥ 6 despite being on 50% oxygen and PEEP of 6 cmH2O and those with > 2 episodes of apnoea needing stimulation or positive pressure ventilation in 24 h were considered as CPAP failure. The prevalence of CPAP failure was determined as a percentage and factors associated were determined by logistic regression. A p-value of < 0.05 was considered significant and 95% confidence interval was used. Results Of the enrolled newborns, 48% were male and 91.4% were in-born. The mean gestational age and weight were 29 weeks (range 24-34 weeks) and 1157.7 g (range 800-1500 g) respectively. Of the mothers 44 (25%) received antenatal corticosteroids. Overall CPAP failure was 37.4% and among those weighing ≤ 1200g, it was 44.1% . Most failure occurred within the first 24 h. No factor was identified to be independently associated with CPAP failure. Mortality among those who failed CPAP was 33.8% and 12.8% among those who did not. Conclusions In resource limited settings like ours with low up take of antenatal corticosteroids and scarce surfactant replacement a significant portion of preterm neonates especially those weighing ≤ 1200 g with RDS fail CPAP therapy.